PHYSICOCHEMICAL ANALYSIS AND WATER QUALITY ASSESSMENT OF SELECTED LOCATION IN MAIDUGURI METROPOLIS USING WEIGHTED ARITHMETIC WATER QUALITY INDEX - Mshelia, Yusuf Madu; Lawan, Daggash Muhammad; Arhyel, Mbursa; Inuwa, Jerry (FUDMA JOURNAL OF SCIENCES, 2023)
Access to safe drinking water is crucial for human health and well-being, however many people around the world including Nigeria face challenges in accessing clean water source. The quality of water is an important public issue and water in Maiduguri is no exception. This study focuses on evaluating the physicochemical parameters of borehole water in Maiduguri. Water samples were collected from three locations namely Polo, Moduganari and Old Maiduguri which were analyzed following standard procedure. The results showed that Temperature, pH, Total Dissolved Solids (TDS), Calcium, Chloride and Manganese levels were within safe limits of 25 oC, 6.5-8.5, 500 mg/l, 200-300 mg/l, 250 mg/l and 0.2 mg/l set by World Health Organization (WHO) and Nigerian Industrial Standard (NIS). However, Old Maiduguri and Moduganari had elevated levels of nitrate 35.95 mg/l and 39.95 mg/l compared to Polo with 22.6 mg/l. Dissolved oxygen levels were quite below the standards of 6.5mg/l in all three locations, while turbidity was within the acceptable limits of 5 NTU. According to the Weighted Arithmetic Index (WAI) Method, the water quality in Polo and Moduganari was classified as poor, with Water Quality Index (WQI) values of 59.67 and 51.56, respectively. On the other hand, the water quality in Old Maiduguri was classified as very poor, with a WQI value of 88.03. These results highlight the varying degrees of water quality across the study locations, emphasizing the need for interventions to improve water quality, particularly in Old Maiduguri, to ensure the well-being of the local population.